Electrografting and morphological studies of chemical vapour deposition grown graphene sheets modified by electroreduction of aryldiazonium salts. (10th April 2015) - Mooste, Marek; Kibena, Elo; Kozlova, Jekaterina; Marandi, Margus; Matisen, Leonard; Niilisk, Ahti; Sammelselg, Väino; Tammeveski, Kaido
Graphical abstract: Highlights: CVD-grown graphene sheets were electrografted with various aryldiazonium salts Redox grafting was applied to form thick nitrophenyl films The reduction of the released radicals was in evidence during the redox grafting Multilayer formation on CVD graphene was confirmed by XPS and AFM measurements Thickness of different aryl layers on CVD graphene varied from few to 30 nm Abstract: This work focuses on investigating the electrografting of chemical vapour deposition (CVD) graphene electrodes grown onto Ni foil (Ni/Gra) with different diazonium salts (including azobenzene diazonium tetrafluoroborate, Fast Garnet GBC sulphate salt, Fast Black K salt, 4-bromobenzene diazonium tetrafluoroborate and 4-nitrobenzenediazonium tetrafluoroborate). Various grafting conditions (e.g. "normal" electrografting in the narrow potential range and redox grafting in the wider potential range) were used. The electrochemical grafting behaviour was similar for all diazonium compounds used, except for the 4-nitrobenzenediazonium tetrafluoroborate when redox grafting was applied. The X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM) and Raman spectroscopy results confirmed the presence of the corresponding aryl layers on Ni/Gra surfaces. The formation of multilayers on Ni/Gra substrates was in evidence since the thickness of different aryl layers varied from few to 30 nm depending on the modification procedures as well as the diazonium compounds used and the XPS analysis revealed a peak at about 400 eV for all aryl-modified Ni/Gra samples suggesting the multilayer formation also through azo linkages.